Объяснение:
№ 3
b₁=64 b₂=32 q=b₂/b₁=32/64=1/2
n=6
S₆=b₁((qⁿ-1)/(q-1))
S₆=64·(((1/2)⁶-1)/(1/2-1))=64((1/64-1)/(-1/2))=64·((-63/64)/(-1/2))=64·(63/32)=
2·63=126 ( B)
№4
a₁=-10 a₅=-4 n=5
a₅=a₁+(n-1)d
-4=-10+(5-1)d
-4=-10+4d
4d=6
d=6/4=1.5
n=8
a₈=a₁+(n-1)d=-10+(8-1)·1.5=-10+7·1.5=-10+10.5=0.5
S₈=(a₁+a₈)n/2=(-10+0.5)8/2=-9.5·8/2=-38 (A)
№5
по теотеме Синусов a/Sina = b/Sin B
3/Sin 60° = x/Sin 45°
3/ (√3/2) = x/ (√2/2)
x=((√2/2)·3) / (√3/2)
x=(3√2/2)×(2/√3)=(3√2)/√3=(3√6)/3=√6 (B)
№6
a₁=6 a₂=2
d=2-6=-4
a₃=a₂+d=2-4=-2 (B)
№ 8
R=4√3 ( формула)
a=R√3 =4√3×√3=4×3=12 см ( А)
№10
АВС подобен А₁В₁С₁ , отсюда А₁В₁/АВ=В₁С₁/ВС=А₁С₁/АС
15/3=А₁В₁/4
А₁В₁=15×4/3=60/3=20 (В)
54 - (-1)² + (-1)³ = 54-1-1=52
3) =5x² -2x+5x-2 -(25-20x+4x²) =5x² +3x-2 -25+20x-4x²=
=x² +23x -27
4) =(2x+y)+(y² -4x²) =(2x+y)+(y-2x)(y+2x)=(2x+y)(1+y-2x)
5) = (2³ -a³) - (3³ + a³) = 8 - a³ - 27 - a³ = - 19 - 2a³
-19 - 2*(-2)³ = -19 - 2*(-8)= -19+16 = -3
6) = =(b-4 -(a+3))(b-4+a+3)=(b-4-a-3)(b+a-1)=(b-a-7)(b+a-1)
7)=x² (x⁴ - y⁴) = x² (x² - y²)(x² + y²)=x² (x-y)(x+y)(x² +y²)